Features of immune status of patients with infectious lesions of large skin folds - G. V. Nosonova (Zaporozhye State Medical University, 2014)
Aim. To examine the features status of patients with infectious lesions of large skin folds. Methods and results. In the study of the immune status of 80 patients with infectious lesions of large skin folds the following was identified: suppression of phagocytes, changes in the quantitative composition of the main populations and subpopulations of lymphocytes, characterized by T-cell deficiency on the background of an increase in CD19+ and CD16+, lower CD4+/CD8+, increase in immunoglobulin G and M, under normal indicators of IgA and significant increase in production of interleukin-10 and 12, which is evidence of hyperactivation of proinflammatory and anti-inflammatory mechanisms of the immune system. Conclusion. The largest dissociation of the above parameters was observed in patients with mixed-forms.